Targeted cash transfers, credit constraints, and ethnic migration in the People Republic of China. - Howell, Anthony
This paper relies on recent proprietary data from the People's Republic of China (PRC) poor rural minority areas to examine the importance of credit constraints on internal labor migration. Specifically, a liquidity shock via the PRC minimum living standard assistance (MLSA) program is decomposed into its direct and indirect parts. The institutional features of the MLSA program permit an identification strategy that relies on a set of verifiable assumptions and an instrument variable framework. The results reveal that the direct effect on migration of MLSA is negative, although the net effect is positive driven by the large indirect effects, which are twice as large for ethnic minorities compared to the Han majority. Subsequent evidence further suggests that the main mechanism behind the indirect effect is informal interpersonal lending fostered by risk sharing strategies. The findings imply that once liquidity is injected into a village it gets circulated in the community, stimulating migration particularly within credit-constrained minority communities.